2018
DOI: 10.1038/s41598-018-33522-8
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime activities and peripheral clock oscillations depend on Wolbachia endosymbionts in flies

Abstract: Wolbachia are ubiquitous bacterial endosymbionts of arthropods and affect host gene expression. Although Wolbachia infections were suggested to modulate sleep in flies, their influence on the circadian clock remained obscure. Here, we screened bacterial symbionts in a laboratory Drosophila melanogaster colony, and observed widespread infections of wMel strain Wolbachia. We established a Wolbachia-free strain from a clock gene reporter strain, period-luciferase (per-luc). Temperature (19–29 °C)-compensated free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
3
15
0
1
Order By: Relevance
“…Hence, the expression pattern of the serine and glycine metabolism genes in heads of GFR flies, rather than WT flies, mimic starvation conditions. Interestingly, in line with this observation, a recent study showed an increase in nighttime activities in non- Wolbachia infected D. melanogaster flies compared to infected [58].…”
Section: Discussionsupporting
confidence: 63%
“…Hence, the expression pattern of the serine and glycine metabolism genes in heads of GFR flies, rather than WT flies, mimic starvation conditions. Interestingly, in line with this observation, a recent study showed an increase in nighttime activities in non- Wolbachia infected D. melanogaster flies compared to infected [58].…”
Section: Discussionsupporting
confidence: 63%
“…This is consistent with the observation that Wolbachia infection resulted in an increase of the number of nighttime sleep bouts (Bi et al, 2018), indicating that Wolbachia infection could decrease the sleep quality in D. melanogaster. Morioka et al (2018) also demonstrated that D. melanogaster carrying Wolbachia exhibited an increase in nocturnal activities relative to uninfected flies, which may reflect a decrease in arousal threshold during the nighttime. Moreover, we also found that Wolbachia infection caused an increase in sleep latency as the night progresses (Bi et al, 2018).…”
Section: The Effect Of Wolbachia On the Sleep Behavior Of Hostsmentioning
confidence: 81%
“…Alternatively, hosts may be modifying their own behavior as a response to Wolbachia infection. Several studies indicate that w Mel alters circadian activity and sleep patterns of D. melanogaster [52,5456]. For example, Bi et al [55] report that w Mel increases sleep time, which could represent a host immune response to infection [19].…”
Section: Discussionmentioning
confidence: 99%